The Impact of Blended Learning on the Academic Performance of Physics Students in the Bwari Area Council of Abuja - Fadipe Bayo Michael (Scientia Publica Media, 2025)
This study examined the impact of blended learning on the academic achievement of Physics students in the Bwari Area Council of the Federal Capital Territory (FCT), Nigeria. The research was guided by two objectives, two research questions, and two hypotheses. The target population consisted of 3,870 Physics students enrolled in secondary schools within the Bwari Area Council. A total of 120 students were randomly selected from four secondary schools that offer Physics as a subject. Data were collected using a 50-item researcher-developed multiple-choice test titled Researcher Made Light and Optics Achievement Test (RMLOAT). The reliability of the instrument was established using the test-retest method, yielding a temporal stability coefficient of 0.88 and an internal consistency coefficient of 0.79. A pretest was also conducted to ensure the appropriateness of the sample. Data analysis involved the use of mean and standard deviation. The findings revealed that blended learning significantly enhanced the academic performance of Physics students in the study area. Additionally, the results indicated no significant differences in performance based on gender, suggesting that blended learning is equally effective for both male and female students. Based on these findings, the study recommends that blended learning be adopted as a mandatory instructional approach in secondary schools, particularly for technology-oriented subjects such as Physics. It also advocates for regular and mandatory training and retraining programs for secondary school teachers on 21st-century instructional strategies, including blended learning.